Access to tablet injectable opioid agonist therapy in rural and smaller urban settings in British Columbia, Canada: a qualitative study - Geoff Bardwell; Jeanette M. Bowles; Manal Mansoor; Dan Werb; Thomas Kerr (BMC, 2023)
Abstract Background Rural and smaller urban settings in Canada are disproportionately impacted by the overdose crisis, highlighting the need for novel public health interventions within these jurisdictions. Tablet injectable opioid agonist therapy (TiOAT) programs have been implemented in select rural communities as a means to address drug-related harms. However, little is known about the accessibility of these novel programs. Therefore, we conducted this study to understand the rural context and factors that affected access of TiOAT programs. Methods Between October 2021 to April 2022, individual qualitative semi-structured interviews were conducted with 32 individuals enrolled in a TiOAT program at participating rural and smaller urban sites in British Columbia, Canada. Interview transcripts were coded using NVivo 12 and data were analyzed thematically. Results TiOAT access varied considerably. TiOAT delivery in rural settings is complicated due to geographic challenges. Participants who were homeless and staying at a nearby shelter or those in centrally-located supportive housing had minimal issues compared to those living in more affordable housing on the outskirts of town with limited transportation options. Dispensing policies that required daily-witnessed ingestion multiple times daily were challenging for most. Only one site provided evening take-home doses whereas participants at the other site could only resort to the illicit opioid supply to address withdrawal outside of program hours. Participants described the clinics as providing a positive and familial social environment compared to experiences of stigma elsewhere. Medication interruptions did occur when participants were in hospital and custodial settings, leading to withdrawal, program discontinuation, and overdose risk. Conclusions This study highlights the beneficial ways in which health services tailored for people who use drugs can create a stigma-free environment with an emphasis on social bonds. Other factors such as transportation access, dispensing policies, and access in rural hospitals and custodial settings produced unique challenges for rural people who use drugs. Public health authorities in rural and smaller settings should consider these factors when designing, implementing, and scaling up future substance use services, including TiOAT programs.